Assessing the knowledge, attitude and practice of contraception in rural India: a necessary step in achieving population control - U., Ashwini Nayak; K. G., Ramakrishnan; K. N., Venkateswar; M., Vijayshree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: India’s projected population will be 1.53 Billion by the year 2050. Every fifth birth in the world is an Indian, and 50% percent of the Indian population are of reproductive age. Objective of present work was to study the knowledge, attitude and practice of contraception among rural women. Methods: 100 rural women in the study were evaluated with the help of a pre-designed and pre-tested questionnaire for the knowledge regarding contraception. Results: Though all women were aware of at least one contraceptive method, 11% never used contraception. The most commonly used contraceptive was condom 59%, followed by 41% CU-T, 27% tubectomy, 18% pills, 10% injectable and 3% emergency contraception. Conclusions: Though knowledge about at least one contraceptive method existed, there is a strong need for motivational strategies to make people accept the methods. Furthermore, there needs to be more educational programs to increase awareness about the existence of various family planning methods.